030: EDUCATING THE COMMON PUBLIC ON MEDICINE USE THROUGH NEWSPAPER WRITING. (24th August 2015) - Mohanta, Guru Prasad
Abstract : Background: The consumers are the ultimate users of medicines. Their understanding helps taking informed decisions to comply with medication orders. It has been reported that around 50% consumers do not take medicines appropriately. Objectives: The present paper aims at discussing the experience of author on newspaper writing on medicine use. Methods: The author made an attempt to write consumer education materials initiating a fortnight column "KNOW YOUR MEDICINE" in one of the widely circulated English daily. Thereafter regular contribution continued in another Newspaper. The writings in simple and user friendly way covered wide range of themes ranging from consumers' right on medicine use, storing medicine at home to clinical trial to the use of individual medicine. Result: The articles have been widely appreciated by various sections of the society including District Collector and Public Health Officer. The appreciation ranged from asking to continue to seek information on various aspects of medicines and their use. The public continued seeking more information through postcards, telephones and e. mail. The readers' queries were replied through the column using a theme. The pensioners' association intended to reproduce one article in their newsletter. The newspaper was apprehensive about the need of such writings in the beginning, but the readership's survey proved the column's popularity. Conclusion: There has been increasing demand of mediicne use educating materials. After a long four year period, the author continued writing in other newspaper attempting empowering public and promoting appropriate use of medicines through public education.